A case of novel coronavirus disease after combination therapy with nivolumab and ipilimumab for metastatic renal cell carcinoma. Issue 2 (30th December 2021) - Kijima, Yu; Shimizu, Tomokazu; Kato, Shinya; Sekido, Eri; Kano, Kana; Toguchi, Makoto; Horiuchi, Toshihide; Toma, Hiroshi; Iida, Shoichi; Takagi, Toshio
Abstract : Introduction: We present a case of novel coronavirus disease‐2019 that underwent combination therapy with nivolumab and ipilimumab for metastatic renal cell carcinoma. Case presentation: A 50‐year‐old man complained of anorexia and weight loss. Contrast‐enhanced computed tomography revealed a solid mass of 57 mm in diameter with cysts in the right kidney, along with liver, lung, and multiple bone metastases. Computed tomography‐guided biopsy of the right kidney was performed, and a diagnosis of clear cell renal cell carcinoma was made. Three weeks after nivolumab and ipilimumab administration, the patient contracted coronavirus disease‐2019. Anticoagulation therapy (dalteparin) was administered for 4 days once infection was confirmed, after which dexamethasone was administered for 10 days. The patient survived without experiencing worsened respiratory symptoms. Conclusion: We administered nivolumab and ipilimumab combination therapy as treatment for metastatic renal cell carcinoma. No side effects or immune‐related adverse events were observed for a short time.